An analysis of the effect of monetary policy changes on macroeconomic factors - Moid U. AHMAD; Shamima NASRIN (Theoretical and Applied Economics, 2017)

(untitled)
One important role of the Reserve Bank of India (RBI) or any central bank is to ensure economic stability in the country. For the purpose, the central bank adopts various measures to ensure that the inflation rates, GDP, interest rates, exchange rates, money supply and other target macroeconomic parameters remain under control. It uses reserve ratios like Cash Reserve Ratio and interest rates like Repo rates to control liquidity and inflation in the country. The effectiveness of such policies and monetary rates in ensuring economic stability needs to be verified and tested. The decision maker needs to understand the effect of these changes on the affected (targeted) variable. This research is an attempt to test and verify the effectiveness of the changes in monetary and policy rates on the desired critical variables. What is the effect and how much is the effect? Can these effects help in better policy making? These are some of the questions aimed to be addressed in the research. The research uses basic statistical tools such as correlation, regression and advance statistical tools such co-integration and Vector Auto Regression to study the variables and draws conclusion based on the results. The data used is from Indian economy and the time period used is 2011-2014. Monthly and quarterly data has been used as required. The research is aimed to provide information to decision makers in formulating policies and to contribute to the existing literature on the subject.